Does innovation in Environmental Technologies Curb CO2 Emissions? Evidence From Advanced Time Series Techniques - Hongqiao, Han; Xinjun, Wang; Ahmad, Mahmood; Zhonghua, Li (Frontiers in Environmental Science, 2022)
This study investigates the impact of environmental innovation, de jure trade globalization, renewable energy consumption and financial development on CO2 emissions in the United States (US) under the Environment Kuznets Curve hypothesis (EKC). To do this, yearly data from 1971 to 2018 is employed using the novel Augmented ARDL (AARDL) and Gradual Shift causality for empirical analysis. The empirical outcomes from the AARDL test disclosed cointegration between variables. The long-run empirical estimation revealed that environmental innovation is contributing to CO2 mitigation. Also, environmental innovation helps to develop the EKC between economic growth and CO2. Apart from this, environmental innovation Granger causes economic growth and CO2. Additionally, financial development is positively connected with CO2, while renewable energy alleviates emissions levels. The study also found a negative association between de jure trade globalization and CO2 emissions only in the short-run. Lastly, various CO2 mitigation strategies are discussed.